2015
DOI: 10.1039/c5cp02224j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the unimolecular reaction of CH2OO and the bimolecular reactions with the water monomer, acetaldehyde and acetone under atmospheric conditions

Abstract: Stabilized Criegee Intermediates (sCIs) have been identified as oxidants of atmospheric trace gases such as SO2, NO2, carboxylic acids or carbonyls. The atmospheric sCI concentrations, and accordingly their importance for trace gas oxidation, are controlled by the rate of the most important loss processes, very likely the unimolecular reactions and the reaction with water vapour (monomer and dimer) ubiquitously present at high concentrations in the troposphere. In this study, the rate coefficients of the unimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
162
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(186 citation statements)
references
References 53 publications
(163 reference statements)
24
162
0
Order By: Relevance
“…Our measured rate coefficients are largely consistent with prior room temperature measurements. At 298 K and 25 Torr, our measurement for CH 2 OO + CH 3 CHO (1.2 ± 0.2) × 10 −12 cm 3 molecule −1 s −1 is consistent within the uncertainties with the indirect measurement by Berndt et al (1.7 ± 0.5) × 10 −12 cm 3 molecule −1 s −1 and in slight disagreement with Stone et al's indirect measurement of (1.48 ± 0.04) × 10 −12 cm 3 molecule −1 s −1 . The kinetics of CH 2 OO +CH 3 CHO were found to be ∼4 times faster than CH 2 OO + CH 3 COCH 3 across all the temperature range studied here.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Our measured rate coefficients are largely consistent with prior room temperature measurements. At 298 K and 25 Torr, our measurement for CH 2 OO + CH 3 CHO (1.2 ± 0.2) × 10 −12 cm 3 molecule −1 s −1 is consistent within the uncertainties with the indirect measurement by Berndt et al (1.7 ± 0.5) × 10 −12 cm 3 molecule −1 s −1 and in slight disagreement with Stone et al's indirect measurement of (1.48 ± 0.04) × 10 −12 cm 3 molecule −1 s −1 . The kinetics of CH 2 OO +CH 3 CHO were found to be ∼4 times faster than CH 2 OO + CH 3 COCH 3 across all the temperature range studied here.…”
Section: Resultssupporting
confidence: 89%
“…In the present work, we report the temperature‐dependent rate coefficients for reactions of CH 2 OO with CH 3 COCH 3 and CH 3 CHO and compare these with similar studies on C2–C4 alkenes (ethene, propene, and butenes) . Existing literature on the carbonyl reactions has been limited to room temperature . Taatjes et al used photoionization mass spectrometry and found the reaction with CH 3 CHO to be four times faster than with CH 3 COCH 3 at P = 4 Torr.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The experiments have been performed in a free-jet flow system at a pressure of 1 bar purified air (or O 2 /N 2 mixtures) and a temperature of 295±2 K (1536). The reaction time was in the range of 3.0–7.9 s. This set-up allows the investigation of oxidation reaction for atmospheric conditions in absence of wall effects.…”
Section: Methodsmentioning
confidence: 99%
“…7 Because SCIs are readily consumed, they have very low steady-state concentrations, 8 and consequently their fate in the atmosphere is not well established. 1 To provide a relatively clean source of SCIs for spectroscopic, 9-21 dynamics, [22][23][24][25][26] and kinetics studies, [27][28][29][30][31][32][33][34][35][36] SCIs are almost exclusively made from photo-oxidation reactions of (R 1 R 2 )CI 2 in the presence of O 2 (where R 1 /R 2 represent hydrogen atoms or alkyl radicals To provide accurate rate constants and to aid experimental measurements, unimolecular decomposition rate constants of syn-CH 3 CHOO under atmospheric conditions are computed here from first principles using Miller's semiclassical transition state theory (SCTST) [41][42][43][44][45] in combination with a two-dimensional master equation (2DME) approach. 7,46 This chemical kinetics analysis is performed using a high accuracy potential energy surface that is constructed with a modification of the HEAT protocol.…”
Section: Introductionmentioning
confidence: 99%